Analysis of Brucine using Poly(L-Arginine) modified biosynthesized CuO nanoparticle composite sensor - Sumanth Devaraj; Jamballi G. Manjunatha; Samar A. Aldossari; Saikh Mohammad; Narges Ataollahi (Journal of Taibah University for Science)
The study investigated the sensitive and selective electrochemical behavior of Brucine (BC) using electrochemically polymerized L-Arginine (LA) modified with a composite comprising biosynthesized copper oxide (CuO) nanoparticles (NPs) and carbon paste electrode (PAMCuONPs/CPE). PAMCuONPs/CPE showed an optimum reversible redox-peak at 0.2 M phosphate buffer solution (PBS) at pH 2.5, allowing detection of BC. The characterization of PAMCuONPs/CPE and bare CuONPs composite carbon paste electrode (BCuONPs/CPE) was performed using scanning-electron microscopy (SEM), X-ray diffraction (XRD), and energy-dispersive spectroscopy (EDS). Electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV), and linear sweep voltammetry (LSV) methods were employed to evaluate the performance of PAMCuONPs/CPE. Experimental parameters, including pH, and variation of concentration, were investigated. PAMCuONPs/CPE exhibited an electrochemical performance with a limit of detection (LOD) of 0.12×10−6 M and a limit of quantification (LOQ) of 0.43×10−6 M. It demonstrated good reproducibility, repeatability, and stability. PAMCuONPs/CPE was successfully validated in determining BC in real samples.